Mindful Journalism and News Ethics in the Digital Era: A Buddhist Approach - Gunaratne, Shelton A. (Routledge Research in Journalism, 2015)
This book aims to be the first comprehensive exposition of ""mindful journalism""-drawn from core Buddhist ethical principles-as a fresh approach to journalism ethics. It suggests that Buddhist mindfulness strategies can be applied purposively in journalism to add clarity, fairness and equity to news decision-making and to offer a moral compass to journalists facing ethical dilemmas in their work. It comes at a time when ethical values in the news media are in crisis from a range of technological, commercial and social factors, and when both Buddhism and mindfulness have gained considerable ac